2012
DOI: 10.1177/0305735612463950
|View full text |Cite
|
Sign up to set email alerts
|

Psychological well-being in professional orchestral musicians in Australia: A descriptive population study

Abstract: We report the major findings from the psychosocial questionnaire component of a cross-sectional population survey of the musicians in Australia's eight full-time professional symphonic and pit orchestras. The response rate was 70% (n = 377). Female musicians reported significantly more trait anxiety, music performance anxiety, social anxiety, and other forms of anxiety and depression than male musicians. The youngest musicians (<30 years) were significantly more anxious compared with the oldest musicians (51+)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
280
6
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(323 citation statements)
references
References 34 publications
16
280
6
21
Order By: Relevance
“…Nonetheless, it is believed that this more select group (relative to music students) deserves special and specific attention, as many of them end up creating their own coping strategies, which often include the indiscriminate use of drugs with no medical supervision 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it is believed that this more select group (relative to music students) deserves special and specific attention, as many of them end up creating their own coping strategies, which often include the indiscriminate use of drugs with no medical supervision 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Mint a szorongásos és depressziós kórképek esetében, a zenei teljesítményszorongás is elsősorban a lányokat, nőket érinti, és ez már egészen kisgyermekkorban megmutatkozik (Kenny, Driscoll és Ackermann, 2014). Az életkor tekintetében a serdülőkort szokták említeni, mint sérülékeny életszakaszt a pszichikai problémák tekintetében, s ez alól a zenei teljesítményszorongás sem kivétel (Papageorgi, Hallam és Welch, 2007).…”
Section: Bevezetésunclassified
“…A gyakorlással és a fellépések számával egyenes arányban az ún. zenei magabiztosság jelentősen nőhet ugyan, de vannak olyan (köztük nagyon sikeres, világhírű) muzsikusok is, akik életük végéig küzdenek ezzel a kihívással (Kenny, Driscoll és Ackermann, 2014;Salmon, 1990).…”
Section: Bevezetésunclassified
“…Music researchers have identified entertainers as 'sensation-seekers' (Miller & Quigley, 2011) and it has been suggested that the lifestyles of gigging entertainers fosters increased alcohol use because of work-related mental health issues (Dobson, 2010;Ewens, 2016;Kenny et al, 2014;Raeburn, 1987). However the precise ways by which entertainers' drinking behaviour is shaped by their working conditions, rather than individual factors, remains unknown.…”
Section: Introductionmentioning
confidence: 99%